Airway dimensions from fetal life to adolescence—A literature overview. Issue 8 (27th May 2018) - Dave, Mital H.; Schmid, Kathrin; Weiss, Markus
Abstract: Background: Data on airway dimensions in pediatric patients are important for proper selection of pediatric airway equipment such as endotracheal tubes, double‐lumen tubes, bronchial blockers, or stents. The aim of the present work was to provide a synopsis of the available data on pediatric airway dimensions. Methods: A systematic literature search was carried out in the PubMed database, Scopus, Embase, Web of Science, Prisma, and Google Scholar and secondarily completed by a reference search. Based on inclusion and exclusion criteria, a final selection of 109 studies with data on pediatric airway dimensions published from 1923 to 2018 were further analyzed. Results: Six different airway measurement methods were identified. They included anatomical examinations, chest X‐ray, computed tomography, magnetic resonance tomography, bronchoscopy, and ultrasound. Anatomical studies were more abundant compared to other methods. Data provided were very heterogeneously presented and powered. In addition, due to different study conditions, they are hardly comparable. Among all, anatomical and computer tomography studies are thought to provide the most reliable data. Ultrasound is an upcoming technique to estimate airway parameters of fetus and premature infants. There was, in general, a lack of comprehensive studies providing a complete range of airway dimensions in larger groups of patients from birth to adolescence. Conclusions: This work revealed a large heterogeneity of studies providing data on pediatric airway dimensions, making it impossible to compare, or assemble them to normograms for clinical use. Comprehensive studies in large population of children are needed to provide full range nomograms on pediatric airway dimensions.